The Inquiline Ant Myrmica karavajevi Uses Both Chemical and Vibroacoustic Deception Mechanisms to Integrate into Its Host Colonies - Casacci, Luca Pietro (Biology (Basel), 2021)
SIMPLE SUMMARY: Although fiercely defended by workers, ant societies can be infiltrated by social parasites that exploit the whole colony and its resources, instead of taking advantage of a single organism. Among them, we studied Myrmica karavajevi, a rare ant species in which the worker caste does not exist, and queens live as “inquilines” within colonies of another ant species, commonly Myrmica scabrinodis. Parasite queens entirely depend on host worker labour. They have evolved many adaptations to be admitted and integrate as members of the host ant society. Indeed, we found that, even at the pupal stage, the parasite is treated as a valuable item in the colony hierarchy, as it is rescued ahead of the colony’s own brood. Moreover, we discovered that M. karavajevi adult queens use two strategies to live undisturbed in the host nest. The parasite smells like the host queens by possessing specific odours and produces sounds similar to those emitted by M. scabrinodis ants, particularly by queens. Through these kinds of mimicking, M. karavajevi advances its rank towards the highest attainable position in the colony’s hierarchy. M. karavajevi is an outstanding example of multimodal deception, which needs a combined behavioural and molecular approach to be fully unravelled. ABSTRACT: Social parasitism represents a particular type of agonistic interaction in which a parasite exploits an entire society instead of a single organism. One fascinating form of social parasitism in ants is the “inquilinism”, in which a typically worker-less parasitic queen coexists with the resident queen in the host colony and produces sexual offspring. To bypass the recognition system of host colonies, inquilines have evolved a repertoire of deceiving strategies. We tested the level of integration of the inquiline Myrmica karavajevi within the host colonies of M. scabrinodis and we investigated the mechanisms of chemical and vibroacoustic deception used by the parasite. M. karavajevi is integrated into the ant colony to such an extent that, in rescue experiments, the parasite pupae were saved prior to the host’s brood. M. karavajevi gynes perfectly imitated the cuticular hydrocarbon profiles of M. scabrinodis queens and the parasite vibroacoustic signals resembled those emitted by the host queens eliciting the same levels of attention in the host workers during playback experiments. Our results suggest that M. karavajevi has evolved ultimate deception strategies to reach the highest social status in the colony hierarchy, encouraging the use of a combined molecular and behavioural approach when studying host–parasite interactions.